2023
DOI: 10.3390/biomedicines11061663
|View full text |Cite
|
Sign up to set email alerts
|

Apabetalone Downregulates Fibrotic, Inflammatory and Calcific Processes in Renal Mesangial Cells and Patients with Renal Impairment

Abstract: Epigenetic mechanisms are implicated in transcriptional programs driving chronic kidney disease (CKD). Apabetalone is an orally available inhibitor of bromodomain and extraterminal (BET) proteins, which are epigenetic readers that modulate gene expression. In the phase 3 BETonMACE trial, apabetalone reduced risk of major adverse cardiac events (MACE) by 50% in the CKD subpopulation, indicating favorable effects along the kidney–heart axis. Activation of human renal mesangial cells (HRMCs) to a contractile phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…52 Consistent with this, in human renal mesangial cells, apabetalone also reduced the gene expression and the protein level of ALP induced by TGFβ. 47 Taken together, these results clearly indicate that apabetalone has a direct effect on the expression of ALP.…”
Section: Diseasementioning
confidence: 65%
See 3 more Smart Citations
“…52 Consistent with this, in human renal mesangial cells, apabetalone also reduced the gene expression and the protein level of ALP induced by TGFβ. 47 Taken together, these results clearly indicate that apabetalone has a direct effect on the expression of ALP.…”
Section: Diseasementioning
confidence: 65%
“…In parallel to the clinical data, another experiment using apabetalone in human renal mesangial cells exposed to tissue growth factor-β (TGFβ) demonstrated that apabetalone prevents upregulation of α-smooth muscle actin, reduces collagen production, and downregulates key inflammatory and fibrotic markers such as IL-6, IL-1β, cyclooxygenase-2, fibronectin, and periostin. 47 Overall, these findings provide more evidence that apabetalone may help in treating renal dysfunction (Table 1).…”
Section: Diseasementioning
confidence: 82%
See 2 more Smart Citations
“…In pooled phase 2 data analyses, APA reduced the rate of cardiovascular events by approximately 60%. However, in the BETOnMACE Phase III study, APA reduced the risk of major adverse cardiac events (MACE) by 50% in the chronic kidney disease subpopulation, indicating a beneficial effect along the kidney–heart axis [ 94 , 95 ]. Certainly, further clinical trials are needed to better investigate the safety and efficacy of APA in the treatment of CVDs.…”
Section: The Role Of Epigenetics In Inflammationmentioning
confidence: 99%